Penatakelolaan Kandang Pada Umkm Peternakan Kelinci Kampung Ciputri: Penelitian - Iqbal Banyu Sunarya (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The problems of cage management in rabbit farming MSMEs in Ciputri Village, Langensari Village, Lembang Sub-district, include inadequate spatial layout, poor sanitation, non-optimal air circulation, and the threat of theft that causes losses. To overcome this, a mentoring program was conducted during May 2024 with a participatory approach based on local needs. This research aims to design and implement a mentoring program for rabbit farming MSMEs with a focus on cage management. The program included community profiling, SWOT analysis, and intervention in the form of cage design improvement, security improvement, and sustainable management education. The results showed that this assistance had a significant positive impact, especially in improving cage safety. After the program, there were no more cases of rabbit loss due to theft. In addition, cage improvements, especially the installation of roofs, have succeeded in protecting livestock from direct rain exposure, so that the temperature inside the cage becomes warmer and more stable, which has an impact on rabbit health. In conclusion, this mentoring program has successfully provided practical and sustainable solutions for MSME-scale rabbit farmers. The resulting improvements in livestock safety and health contribute to business sustainability and make these MSMEs a model for community empowerment and local economic development.